PENGARUH PEMBERIAN EDUGAME TENTANG MENARCHE TERHADAP KESIAPAN MENGHADAPI MENARCHE DI SDN KANDRI 01 GUNUNGPATI SEMARANG - Esti Musfir, Menik Kustriyani, (Jurnal Ilmu dan Teknologi Kesehatan, 2012)
GIVING EFFECT ON MENARCHE EDUGAME READINESS FOR DEALING IN SDN KANDRI MENARCHE 01 GUNUNGPATI SEMARANGNowadays, the age of children for getting a menarche is earlier than the before generation. Moreover, the female students who are in Elementary School have gotten a menstruation. Therefore, they must prepare their selves to face the menarche. They also have to be given an edugame about menarche. The purpose of this research is to find out what the influence of giving an edugame about menarche to the readiness of the female students in SDN Kandri 1 Gunungpati Semarang. The research that to be used is a pre-experiment with one group pretest-posttest, and taking a sample using sampling total technique. Therefore, we found 43 respondents. For collecting data like questioner and analyzed using a Wilcoxon experiment. The majority of the respondents are 10 year old girls. There are menarche. The minimum grade is 20 and the maximum one is 34, while most respondents are not ready that there are 31 students 72,1%, after being given the edugame on menarche the minimum grade is 28 and the maximum one is 27, while most of the ready respondents are 25 female students 58,1%. The research shows us that there is an influence of giving an edugame about menarche to the readiness of the female students in facing of menarche with p value = 0.000 < 0.05 with ready category after giving the edugame on menarche. Based on this research, we suggest that this data can be used as a foundation to prepare young people especially a girl to face the menarche. Keywords: edugame, menarche, readiness.